INVESTIGATING PRESENCE OF CORRELATIONS AMONG FUNCTIONAL STATUS, DISEASE DURATION, ESR, VALUE OF BMD, LEVEL OF OSTEOCALCIN AND CRP IN PATIENTS WITH RHEUMATOID ARTHRITIS - Savaş Gürsoy; Mehmet Adam (Archives of Rheumatology, 2000)
Aim of the study was to investigate the correlation of functional status (FS), disease duration (DD), menopause duration (MD), level of osteocalcin, CRP, ESR, and value of bone mineral density (BMD) in patients with RA PatientsÕ functional status can be defined with Steinbrocker criteria. Disease duration, vertebrae and femur BMD were measured. Level of the serum osteocalcin (OC), CRP and ESR were measured in 20 patients with RA. In study, we found that vertebra BMD was negatively corelated with menopause duration (r: - 0.46), age (r: - 0.43) and height (r: - 0,5). We also found a significant correlation among FS, CRP, ESR and disease duration (F: 3.52 p<0.05) We observed an insignificant correlation among level of the serum OC,CRP and ESR.